2016
DOI: 10.1073/pnas.1521668113
|View full text |Cite
|
Sign up to set email alerts
|

Cranial grafting of stem cell-derived microvesicles improves cognition and reduces neuropathology in the irradiated brain

Abstract: Cancer survivors face a variety of challenges as they cope with disease recurrence and a myriad of normal tissue complications brought on by radio-and chemotherapeutic treatment regimens. For patients subjected to cranial irradiation for the control of CNS malignancy, progressive and debilitating cognitive dysfunction remains a pressing unmet medical need. Although this problem has been recognized for decades, few if any satisfactory long-term solutions exist to resolve this serious unintended side effect of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 31 publications
3
95
0
Order By: Relevance
“…To circumvent such caveats, work by Baulch et al . demonstrated the promise of using transplanted human neural stem cell-derived microvesicles, in place of stem cells [48]. Intrahippocampal grafting of microvesicles ameliorated the cognitive decrements associated with cranial radiation exposure, decreased neuroinflammation, and preserved dendritic morphology in rats.…”
Section: Stem Cells In the Irradiated Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…To circumvent such caveats, work by Baulch et al . demonstrated the promise of using transplanted human neural stem cell-derived microvesicles, in place of stem cells [48]. Intrahippocampal grafting of microvesicles ameliorated the cognitive decrements associated with cranial radiation exposure, decreased neuroinflammation, and preserved dendritic morphology in rats.…”
Section: Stem Cells In the Irradiated Cnsmentioning
confidence: 99%
“…Intrahippocampal grafting of microvesicles ameliorated the cognitive decrements associated with cranial radiation exposure, decreased neuroinflammation, and preserved dendritic morphology in rats. The transplanted microvesicles were found to migrate throughout the hippocampus and fuse with host brain cells, as determined by tracking a fluorescent marker protein expressed on the surface of the grafted microvesicles [48]. The foregoing data provided some provocative insight into the mechanisms of cognitive improvement following irradiation, and suggested that the bioactive cargo within microvesicles conferred neurotrophic support to the host brain.…”
Section: Stem Cells In the Irradiated Cnsmentioning
confidence: 99%
“…These grafts led to improved performance on behavioral tasks, as well as a reduction in inflammation and retention in neuronal morphology (134). Exosome grafting has led to similar improvements (135). …”
Section: Meeting Program Overview4mentioning
confidence: 98%
“…In another milestone study, Ratajczak et al showed that MVs from ESCs can reprogram hematopoietic stem cells and increase their pluripotency through horizontal transfer of mRNAs [3]. In addition to ESCs, human neural stem cells can generate MVs that have neurocognitive benefits and ameliorate radiation-induced cognitive deficits brought on during radio-and chemo-therapeutic treatment of brain cancers [15].…”
Section: Intrinsic Function Of Stem Cell Derived Mvsmentioning
confidence: 99%